GROUNDWATER QUALITY ASSESSMENT IN DISTRICT SANGHAR, SINDH, PAKISTAN USING MULTIVARIATE STATISTICS (Journal of Medical & Health Sciences Review, 2025)
The present study investigates the groundwater quality of various Union Councils in Sanghar District, Sindh, Pakistan, with a focus on evaluating its suitability for human consumption. A total of 99 groundwater samples were collected and analyzed for key physicochemical parameters, including pH, electrical conductivity (EC), total dissolved solids (TDS), hardness, chloride, fluoride, sulphate, nitrate, and arsenic. Comparative assessment with World Health Organization (WHO) drinking water standards revealed that while the average concentrations of most parameters remained within permissible limits, approximately 20.20% of the samples exceeded the recommended TDS threshold of 1000 mg/L, indicating potential health risks. EC values ranged from 450 to 4980 µS/cm, with an average of 1764.4 µS/cm. A strong positive correlation (r > 0.75) was observed between TDS and EC, chloride, hardness, and sulphate, likely due to the dissolution of salts originating from similar geological formations. Additionally, EC showed a positive correlation with both hardness and chloride. Multivariate statistical approaches, including cluster analysis, coefficient of determination, and principal component analysis (PCA), were employed to interpret spatial patterns and interrelationships among the parameters. Cluster analysis effectively grouped sampling locations with similar water quality characteristics, aiding in the identification of zones requiring targeted monitoring and intervention. The findings highlight the necessity for continuous water quality surveillance and the implementation of appropriate mitigation strategies in areas where groundwater contains elevated salt and fluoride levels. Long-term consumption of such water may contribute to adverse health outcomes, underscoring the importance of sustainable water resource management in the region.